Conditional inactivation of the L‐type amino acid transporter LAT1 in chondrocytes models idiopathic scoliosis in mice. Issue 11 (26th September 2022) - Iwahashi, Sayuki; Lyu, Jiajun; Tokumura, Kazuya; Osumi, Ryoma; Hiraiwa, Manami; Kubo, Takuya; Horie, Tetsuhiro; Demura, Satoru; Kawakami, Noriaki; Saito, Taku; Park, Gyujin; Fukasawa, Kazuya; et al.
Abstract: Scoliosis, usually diagnosed in childhood and early adolescence, is an abnormal lateral curvature of the spine. L‐type amino acid transporter 1 (LAT1), encoded by solute carrier transporter 7a5 ( Slc7a5 ), plays a crucial role in amino acid sensing and signaling in specific cell types. We previously demonstrated the pivotal role of LAT1 on bone homeostasis in mice, and the expression of LAT1/ SLC7A5 in vertebral cartilage of pediatric scoliosis patients; however, its role in chondrocytes on spinal homeostasis and implications regarding the underlying mechanisms during the onset and progression of scoliosis, remain unknown. Here, we identified LAT1 in mouse chondrocytes as an important regulator of postnatal spinal homeostasis. Conditional inactivation of LAT1 in chondrocytes resulted in a postnatal‐onset severe thoracic scoliosis at the early adolescent stage with normal embryonic spinal development. Histological analyses revealed that Slc7a5 deletion in chondrocytes led to general disorganization of chondrocytes in the vertebral growth plate, along with an increase in apoptosis and a decrease in cell proliferation. Furthermore, loss of Slc7a5 in chondrocytes activated the general amino acid control (GAAC) pathway but inactivated the mechanistic target of rapamycin complex 1 (mTORC1) pathway in the vertebrae. The spinal deformity in Slc7a5 ‐deficient mice was corrected by genetic inactivation of the GAAC pathway, but not by genetic activation of the mTORC1 pathway. These findings suggest that the LAT1‐GAAC pathway in chondrocytes plays a critical role in the maintenance of proper spinal homeostasis by modulating cell proliferation and survivability. Abstract : Inactivation of LAT1/ Slc7a5 in chondrocytes led to severe scoliosis and a general disorganization of chondrocytes in the vertebral growth plate, along with an increase in apoptosis and a decrease in cell proliferation. In addition, LAT1/ Slc7a5 deficiency activated the GAAC pathway and inactivated the mTORC1 pathway. Scoliosis in LAT1/ Slc7a5 deficient mice was rescued by genetic inactivation of the GAAC pathway, but not by genetic activation of the mTORC1 pathway.